'Lost in the marketplace of ideas: Towards a new constitution for free speech after Trump and Twitter?'. (May 2022) - Macedo, Stephen
Democracy is in crisis and one core feature is a communications crisis: a failure of institutions to reliably generate and curate the circulation of information and communications. Capitalism, the internet and Covid have all been unkind to journalism: newspapers and their reporters have been decimated. Newer media – such as Facebook, Twitter and Google – have amassed enormous power in a remarkably short time. They are the new gatekeepers of free expression, as witnessed by the Twitter ban of Donald Trump. Social media platforms are also the bullhorns of disinformation: they seem to exacerbate polarization, sow distrust, speed the spread of misinformation and encourage conspiracist thinking. Can the media companies be trusted to self-regulate? What alternatives do we have? I argue in the end that the Facebook Oversight Board offers a hopeful model.